Impact of the Covid-19 Pandemic on Changes in Weight, Consumption and Lifestyle in Indonesian Students - Sitoayu, Laras; Mardiyah, Sarah; Melani, Vitria; Dewanti, Lintang Purwara; Ronitawati, Putri; Amelia, Sry Rizki; Risda, Rahmatia (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The Covid-19 pandemic that has hit various parts of the world, including Indonesia, has had an impact on society. One of the layers of society that has experienced this impact is students. With the large-scale social restrictions, Indonesian students do a lot of activities at home. Many students become concerned with themselves, but there are also students who feel bored because of low social interaction which in turn causes high food consumption and sedentary behaviour at home. The objective of this study to determine changes in body weight, food consumption and lifestyle in Indonesian students. The design of this study was cross sectional, with descriptive analysis conducted on 1185 students in Indonesia. The results of the study stated that the pandemic had an impact on Indonesian students. During the pandemic as many as 67.1% of students experienced changes in the size of their BB. Most of the students experienced moderate stress (77.1%), and bad sedentary behaviour by 63.4%. However, diet and exercise habits have changed for the better as much as 52.6% and 63.7%, respectively. Indonesian students need to pay more attention to changes in body weight and lifestyle during the pandemic so as not to have a negative impact on health and nutritional status.